Research on Teacher Identity Mapping Challenges and Innovations (Springer International Publishing, 2018)
Understanding teachers' professional identities and their development is key to unpacking teachers' professional lives, the quality of their instruction, their motivation and commitment to teach, and their career decision making. This book features a number of scholars from around the world who represent a variety of disciplines, scientific paradigms, and inquiry methods in researching teacher identity. By bringing these chapters together, this volume initiates active scholarly conversations and extends the boundaries of teacher identity research and practice. This collection of chapters provides significant insight into teacher identity and will be essential reading for pre-service and in-service teachers, teacher educators, school administrators, professional developers, and policy makers at various levels. .